Design as future-making - Yelavich, Susan; Adams, Barbara; Appadurai, Arjun 1949- (Bloomsbury, 2014)
"Design as Future-Making is a collection of essays by an international roster of leading designers and theorists who share a new understanding of design as a socio-material practice embedded within a multiplicity of ways of making the world.Issues such as social justice, environmental health, political agency, education, and even the right to pleasure and play, are customarily thought of as dematerialised ideas and values. Yet, each of those realms of daily life are affected by - indeed, determined by - their physical and virtual contexts. Design as Future-Making argues that design is not only integral to social issues, but it is also an integrated mode of thought and action - one that variously draws on and informs disciplines such as philosophy, sociology, anthropology, political science, and psychology"--